Efficacy and safety of edoxaban compared with warfarin according to the burden of diseases in patients with atrial fibrillation: insights from the ENGAGE AF-TIMI 48 trial. Issue 3 (5th November 2019) - Nicolau, André M; Corbalan, Ramon; Nicolau, Jose C; Ruff, Christian T; Zierhut, Wolfgang; Kerschnitzki, Michael; Duris, Tibor; Juul-Möller, Steen; Voitk, Juri; Trevisan, Marco; Nordio, Francesco; Antman, Elliott M; et al.
Abstract: Aims: Non-vitamin K antagonist oral anticoagulants represent a new option for prevention of embolic events in patients with atrial fibrillation (AF). However, little is known about the impact of non-cardiac comorbidities on the efficacy and safety profile of these drugs. Methods and results: In a post hoc analysis of the ENGAGE AF-TIMI 48 trial, we analysed 21 105 patients with AF followed for an average of 2.8 years and randomized to either a higher-dose edoxaban regimen (HDER), a lower-dose edoxaban regimen, or warfarin. We used the updated Charlson Comorbidity Index (CCI) to stratify the patients according to the burden of concomitant disease (CCI = 0, 1, 2, 3, and ≥4). The treatment groups were then compared for safety, efficacy, and net clinical outcomes across CCI categories. There were 32.0%, 7.3%, 42.1%, 12.7%, and 6.0% of patients with CCI scores of 0, 1, 2, 3, and ≥4, respectively. A CCI score ≥4 was associated with significantly higher rates of thromboembolic events, bleeding, and death compared to CCI = 0 ( P  < 0.05 for each). The annualized rates of the primary net clinical outcome (stroke/systemic embolism, major bleeding, or death) for CCI = 0, 1, 2, 3, or ≥4 were 5.9%, 8.7%, 6.6%, 10.3%, and 13.6% ( P trend < 0.001). There were no significant interactions between treatment with HDER vs. warfarin and efficacy, safety, and net outcomes across the CCI groups ( P -interaction > 0.10 for each). Conclusion : Although increasing CCI scores are associated with worse outcomes, the efficacy, safety, and net clinical outcomes of edoxaban vs. warfarin were independent of the degree of comorbidity present.